(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Ecotourism sites in Samarkand Region lose competitiveness when reception, guiding, transport, and booking operate as disconnected functions instead of one guest-facing chain. To examine this service gap, a mixed-method case study combined a questionnaire, semi-structured interviews, and content analysis. Descriptive results showed the weakest point in booking convenience (2.10–4.60), while reception coordination was stronger (2.70–4.90) and perceived service quality stayed within 2.40–4.80. The regression model accounted for a substantial part of the variance (R² = 0.47). Coordination was the dominant predictor (β = 0.41, p<0.001), transport accessibility also contributed significantly (β = 0.28, p = 0.006), and the remaining service dimensions were less influential. These results support integrated reservation, guide scheduling, and access management as the most effective route to better visitor experience and more stable ecotourism performance.